2009
DOI: 10.1002/hep.22959
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term therapy with clevudine for chronic hepatitis B can be associated with myopathy characterized by depletion of mitochondrial DNA†

Abstract: Clevudine (Revovir), a pyrimidine nucleoside analogue, is a recently introduced antiviral drug. Clinical trials have demonstrated potent, sustained antiviral activity against hepatitis B virus without specific adverse events. The lack of cytotoxicity and absence of an effect on mitochondrial function have been considered the reasons for the fewer adverse events. However, it came to our attention that several hepatitis B patients developed myopathy during clevudine therapy.Our study was aimed to analyze the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 23 publications
3
85
2
Order By: Relevance
“…5,6,9,10 And our study shows that telbivudine is not an exception from antiviral-induced mitochondrial toxicity. This nucleoside analogue-related cellular toxicity is related to decreased mtDNA content (Fig.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…5,6,9,10 And our study shows that telbivudine is not an exception from antiviral-induced mitochondrial toxicity. This nucleoside analogue-related cellular toxicity is related to decreased mtDNA content (Fig.…”
Section: Discussionmentioning
confidence: 49%
“…3,4 Previous pathological studies have shown that the myopathy associated with nucleoside/nucleotide analogues is mostly due to the mitochondrial toxicity. 5,6 However, previous pathological reports on telbivudine-induced myopathy did not clearly reveal the evidence of mitochondrial toxicity. 7,8 Here, we showed that the myopathy induced by prolonged use of telbivudine is a mitochondrial myopathy caused by disturbed replication of mitochondrial DNA.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…9,12,13,24,25 However, severa l hepatitis B patients develop myopathy during long-term clevudine therapy. 26,27 Moreover, long-term clevudine therapy induces depletion of mitochondrial DNA and leads to mitochondrial myopathy associated with myonecrosis. 26 In our study, one CHI/HCC (1.9%) patient discontinued clevudine treatment due to symptomatic myopathy.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Moreover, long-term clevudine therapy induces depletion of mitochondrial DNA and leads to mitochondrial myopathy associated with myonecrosis. 26 In our study, one CHI/HCC (1.9%) patient discontinued clevudine treatment due to symptomatic myopathy. His clinical symptoms subsequently improved after clevudine withdrawal, and no residual symptoms remained.…”
Section: 16mentioning
confidence: 99%